Tetrazole conjoined organosilane and organosilatrane via the 'click approach': a potent Mycobacterium tuberculosis enoyl ACP reductase inhibitor and a dual sensor for Fe(iii) and Cu(ii) ions. (10th January 2022) - Singh, Gurjaspreet; Priyanka,; Sushma,; Pawan,; Diksha,; Suman,; Mohit,; Devi, Anita; Gupta, Sofia
Abstract : This article includes the synthesis and characterization of tetrazole-allied organosilane and organosilatrane. The tetrazole-allied silatrane was explored for molecular docking and optical aspects. Abstract : Tetrazoles are a class of heterocycles that are important in medicinal chemistry and drug design due to their metabolic stability and other beneficial physicochemical properties. Organosilicon chemistry is an amalgamation of different moieties and has vast applications. The amalgamation of pharmacologically active tetrazole segments with optically active higher coordinated silicon atoms can synergistically enhance their applicability in certain fields. As such, in this article, we have designed and synthesized a novel series of tetrazole conjoined organosilane and organosilatrane using ZnBr2 as a catalyst via the click reaction. The all new compounds were confirmed using IR, 1 H NMR and 13 C NMR and mass spectrometry. The designed tetrazole appended organosilatrane (3 ) was explored for recognition potential and found to be specific and selective for Fe(iii ) and Cu(ii ) metal ions. The low detection limits, high association constants, negligible competitive interference and reversible behavior of the sensor confirm its recognition efficiency only towards Fe(iii ) and Cu(ii ). Job's plot confirmed the 1 : 1 stoichiometric binding of the host : guest system. To explore the biological results of tetrazole-based organosilatrane, a molecular docking study with the enoyl acyl carrier protein reductase of Mycobacterium tuberculosis was performed and the selected ligand was found to have a good docking score with a binding energy of −7.82 kcal mol −1 .